Crag Martin neontology complements taphonomy at the Gorham's Cave Complex - Keith Bensusan (Nature Portfolio, 2021)
Abstract Species present in the fossil record may continue to exist at an archaeological site, allowing study that fine-tunes our picture of the ecological past. A large wintering population of Eurasian Crag Martins Ptyonoprogne rupestris (ECM) roosts at the ‘Gorham’s Cave Complex’ UNESCO World Heritage site in Gibraltar, which is best known for its occupation by Neanderthals at times when ECMs were also present. Its complex geomorphology allows the study of use of different micro-sites (caves) within the roost. We used mark-recapture to test whether birds showed fidelity to micro-sites for roosting, and for differences in condition of birds across micro-sites. ECM showed very high fidelity towards micro-sites, within and between years, with > 90% chance of recapture at caves where they were first caught. Condition of birds differed between micro-sites, suggesting differences in roost quality between caves; birds were more likely to be recaptured at the micro-site where birds were in best condition, indicating higher survivorship. Our results demonstrate extremely fine-scale fidelity at the largest roosting site documented for ECM globally. Implications for conservation are discussed. The study provides current knowledge of a bird that has been using these caves since the Pleistocene and more generally on these caves as refuges.